144 LONG-TERM PROGNOSTIC IMPACT OF SUBCLINICAL MYOCARDIAL DYSFUNCTION IN PATIENTS RECOVERED FROM COVID-19. (15th December 2022) - Cannata, Francesco; Pinto, Giuseppe; Chiarito, Mauro; Maurina, Matteo; Condello, Francesco; Bombace, Sara; Villaschi, Alessandro; Novelli, Laura; Stankowski, Kamil; Liccardo, Gaetano; Gasparini, Gaia; Donia, Dario; et al.
Abstract: Aims: Cardiovascular sequelae may occur in patients recovered from COVID-19. Recent studies have detected a considerable incidence of subclinical myocardial dysfunction – assessed with speckle-tracking echocardiography – and of long-COVID symptoms in these patients. This study aimed to define the long-term prognostic role of subclinical myocardial dysfunction and long-COVID condition in patients recovered from COVID-19 pneumonia. Methods and Results: We prospectively followed-up 110 patients hospitalized at our Institution due to COVID-19 pneumonia in April 2020 and then recovered from SARS-CoV-2 infection. A 6-month clinical and echocardiographic evaluation was performed, followed by a 21-month clinical follow-up. The primary outcome was major adverse cardiovascular events (MACE), a composite of myocardial infarction, stroke, heart failure hospitalization and all-cause mortality. A subclinical myocardial dysfunction – defined as an impairment of left ventricular global longitudinal strain (≥ -18%) - was identified at 6-month follow-up in 37 patients (34%), was associated with an increased risk of long-term MACE with a good discriminative power (AUC: 0.73) and resulted a strong independent predictor of extended MACE in a multivariate regression analysis (OR 9.29, 95%CI 2.20–39.3, p=0.002). Long-COVID condition was not associated with a worse long-term prognosis, instead. Conclusion: In patients recovered from COVID-19 pneumonia, a subclinical myocardial dysfunction is present in one third of the whole population at 6-month follow-up and is associated with a higher risk of MACE at long-term follow-up. Speckle-tracking echocardiography is a promising tool to optimise the risk-stratification in patients recovered from COVID-19 pneumonia, while the definition of a long-COVID condition has not prognostic relevance.